Investment and monetary policy in the euro area - Benoît Mojon; Frank Smets; Philip Vermeulen (European Central Bank (ECB), 2001)
This paper analyses the effects of a change in monetary policy on firms' investment in Germany, France, Italy and Spain using a data set which provides aggregated balance sheet and profit and loss account data for 17 different industries and 3 different size classes. The main findings are twofold. First, in each of the four countries a change in the user cost of capital, which in turn is affected by interest rates, has both statistically and economically significant effects on investment. Second, while the average interest rate on debt is generally higher for small firms than for large firms, there is little evidence that the effects of monetary policy on small firms are larger
Keywords: E52; 330